2020
DOI: 10.1177/0003134820956355
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing a Small Community Hospital Surgical Residency Program in an Epicenter of the COVID-19 Pandemic

Abstract: Background COVID-19 put a stop to the operative experience of surgical residents, leaving reassignment of the team, to the frontlines. Each program has adapted uniquely; we discuss how our surgical education changed in our hospital. Study Design A retrospective review of changes in general surgery cases, bedside procedures, and utilization of residents before and during the pandemic. Procedures were retrieved from electronic medical records. Operating room (OR) cases 1 month before and 5 weeks after the execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The majority of residents reported that the impact of COVID-19 in their training was severe. 37 Melissa K Meghpara (Nov. 2020) [ 45 ] Surgery Non- questionnaire > 1,000,000 Repurposing the surgical department for the concerns of the pandemic has involved all surgical staff. The strengths of the repurposing allowed the team to meet the demands posed by the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of residents reported that the impact of COVID-19 in their training was severe. 37 Melissa K Meghpara (Nov. 2020) [ 45 ] Surgery Non- questionnaire > 1,000,000 Repurposing the surgical department for the concerns of the pandemic has involved all surgical staff. The strengths of the repurposing allowed the team to meet the demands posed by the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…However, these questionnaire studies had some limitations, such as subjective questions, voluntary response bias, and heterogeneity of respondents and institutional bias, which may limit their generalizability [ 74 ]. Only nine studies had conducted objective investigations and had “real numbers” comparing the prepandemic and pandemic periods [ 17 , 31 , 36 , 39 , 45 , 49 , 50 , 54 , 61 ]. These studies indicated the severity of the effect and identified domains that were affected.…”
Section: Discussionmentioning
confidence: 99%
“…In order to preserve personal protective equipment, reallocate resources and staff, and minimize exposure to the patient and hospital employees, surgical interventions were limited to emergent and urgent cases during the initial surge of the pandemic [ 1 ]. Simultaneously, general surgery residents have a unique and broad skillset that encompasses in-depth knowledge of critical care and bedside procedures (e.g., central lines) that make them an invaluable resource during these demanding times [ 8 ]. As seen in the presented data, this led to dramatic changes in clinical assignments, operative experience, and the educational format for general surgery residents.…”
Section: Discussionmentioning
confidence: 99%